Evaluating the Psychological Impacts Related to COVID-19 of Vietnamese People Under the First Nationwide Partial Lockdown in Vietnam - Le, Xuan Thi Thanh; Dang, Anh Kim; Toweh, Jayson; Nguyen, Quang Nhat; Le, Huong Thi; Do, Toan Thi Thanh; Phan, Hanh Bich Thi; Nguyen, Thao Thanh; Pham, Quan Thi; Ta, Nhung Kim Thi; Nguyen, Quynh Thi; Nguyen, Anh Ngoc; et al. (Frontiers in Psychiatry, 2020)
This is the first time in Vietnam that people have undergone "social distancing" to minimize the spreading of infectious disease, COVID-19. These deliberate preemptive strategies may have profound impacts on the mental health of the population. Therefore, this study aimed to identify the psychological impacts of COVID-19 on Vietnamese people and associated factors. We conducted a cross-sectional study during a one-week social distancing and isolation from April 7 to 14, 2020, in Vietnam. A snowball sampling technique was carried out to recruit participants. Impact of Event Scale-Revised (IES-R) was utilized to assess the psychological impacts of the COVID-19. Of all participants, 233 (16.4%) reported PTSD clinical symptomology; 76 (5.3%) rated as probably having PTSD diagnosis; 77 (5.4%) reported extreme psychologicall conditions. Being female, above 44 years old, or having a greater number of children in the family were positively associated with a higher level of psychological distress. In addition, being self-employed/unemployed/retired was associated with a higher score of intrusion and hyperarousal sub-scale, while having a history of touching objects with the possibility of spreading coronavirus (utensils) related to a higher level of avoidance. There were relatively high rates of participants suffering from PTSD during the first national lockdown related to COVID-19. Comprehensive strategies for the screen of psychological problems and epidemiological monitoring of mental health are critical, especially among the high-risk groups for early intervention.